BRCA1 deficiency in skin epidermis leads to selective loss of hair follicle stem cells and their progeny - Sotiropoulou, Panagiota A. (Cold Spring Harbor Laboratory Press, 2013)
The accurate maintenance of genomic integrity is essential for tissue homeostasis. Deregulation of this process leads to cancer and aging. BRCA1 is a critical mediator of this process. Here, we performed conditional deletion of Brca1 during epidermal development and found that BRCA1 is specifically required for hair follicle (HF) formation and for development of adult HF stem cells (SCs). Mice deficient for Brca1 in the epidermis are hairless and display a reduced number of HFs that degenerate progressively. Surprisingly, the interfollicular epidermis and the sebaceous glands remain unaffected by Brca1 deletion. Interestingly, HF matrix transient amplifying progenitors present increased DNA damage, p53 stabilization, and caspase-dependent apoptosis compared with the interfollicular and sebaceous progenitors, leading to hyperproliferation, apoptosis, and subsequent depletion of the prospective adult HF SCs. Concomitant deletion of p53 and Brca1 rescues the defect of HF morphogenesis and loss of HF SCs. During adult homeostasis, BRCA1 is dispensable for quiescent bulge SCs, but upon their activation during HF regeneration, Brca1 deletion causes apoptosis and depletion of Brca1-deficient bulge SCs. Our data reveal a major difference in the requirement of BRCA1 between different types of epidermal SCs and progenitors and during the different activation stages of adult HF SCs.